Ketidaksesuaian Kualifikasi Guru Pembimbing Khusus (GPK) Dengan Kebijakan Pendidikan Inklusif di Sekolah Swasta - Qita Riambada Tsurayya Dewi; Ahmad Nurabadi; Rochmawati Rochmawati (Varied Knowledge Journal, 2026)
This study aims to analyze the mismatch between the qualifications of Special Education Teachers (Guru Pembimbing Khusus/GPK) and the legal framework of inclusive education in Indonesia, particularly in private schools. Although GPK qualification standards are clearly regulated in Permendiknas Number 70 of 2009, discrepancies frequently occur in practice. This study employs a Systematic Literature Review (SLR) by examining national and international journal articles, policy documents, and official reports related to inclusive education and GPK qualifications. The analysis focuses on differences in GPK recruitment practices between public and private schools, factors contributing to qualification mismatch, and its implications for educational services for children with special needs. The findings indicate that public schools generally employ GPK with Special Education (PLB) backgrounds in accordance with regulations, while private schools often recruit non-PLB graduates due to limited availability of qualified personnel and institutional flexibility. This mismatch affects the quality of assessment, individualized education planning, and curriculum adaptation. The study concludes that a significant gap exists between regulatory standards and field implementation, highlighting the need for strengthened training, certification, and policy supervision to ensure effective and equitable inclusive education.